2009
DOI: 10.1590/s0104-42302009000300023
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicações exógenas em crianças menores de seis anos atendidas em hospitais da região metropolitana do Rio de Janeiro

Abstract: ResumoObjetivO. Descrever o perfil dos casos de intoxicações exógenas de crianças admitidas em hospitais de emergência da região metropolitana do Rio de Janeiro, durante três anos. MétOdOs. Realizou-se levantamento dos dados a partir dos boletins de atendimento de emergência, tendo sido identificados os casos suspeitos ou confirmados de intoxicação nas seguintes categorias: drogas, medicamentos e substâncias biológicas; solventes orgânicos e hidrocarbonetos halogenados; produtos químicos; monóxido de carbono e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
22

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
3
11
0
22
Order By: Relevance
“…Among the agents involved, the results were similar to other studies 2,[9][10][11]15,17,18 that mention medications as the most common agents found in the notifications of food poisoning by toxic substances. However, this information differs from SINAN, which registers food and beverages among the main toxic agents in Brazil with approximately 10.0% of the notifications.…”
Section: Discussionsupporting
confidence: 87%
“…Among the agents involved, the results were similar to other studies 2,[9][10][11]15,17,18 that mention medications as the most common agents found in the notifications of food poisoning by toxic substances. However, this information differs from SINAN, which registers food and beverages among the main toxic agents in Brazil with approximately 10.0% of the notifications.…”
Section: Discussionsupporting
confidence: 87%
“…Diel et al e Lima et al (2,10) intoxicaram-se por raticidas (12) . Resultados bastante inferiores foram encontrados por Werneck e Hasselmann (13) , onde das intoxicações exógenas em crianças menores de cinco anos, 15% dos casos foram por algum tipo de raticida, sendo mais da metade por chumbinho. (4) , casos/100.000 habitantes), com maior concentração na zona urbana (coeficiente de incidência de 2,95casos/100.000 habitantes) (11) .…”
Section: Resultsunclassified
“…Embora não existam estimativas válidas da sua incidência, especula-se que cerca de 500 mil pessoas morrem por este problema a cada ano, o que torna este agravo um problema de saúde pública no mundo (1) .…”
Section: Introductionunclassified
“…9 Several reports have demonstrated that pesticide poisoning has been a long-standing problem through Africa, 10 Asia, 11,12 Europe 13 and Americas. 14,15 Recently, in Sri Lanka, carbofuran, carbosulfan and fenobucarb were detected in plasma samples from patients with a history of acute carbamate self-poisoning suggesting a mixed exposure. Carbofuran was detected in 158 samples at a concentration ranging from 20.7 to 62,200 ng mL -1 .…”
Section: Introductionmentioning
confidence: 99%
“…9,15 These compounds are commonly found in foods and beverages in cases of accidental or intentional intoxication. 17 Over the last years, 157 cases involving aldicarb-contaminated commercial products, and liquid or solid foodstuffs (meat, coffee, milk, soup, juice, cookies, and chocolate) were reported in the Rio de Janeiro State.…”
Section: Introductionmentioning
confidence: 99%